Modulating autism spectrum disorder pathophysiology using a trace amine-focused approach: targeting the gut - L. Pretorius; J. A. Coetzee; A. P. dos Santos; C. Smith (Molecular Medicine)
Abstract Autism spectrum disorder (ASD) affects approximately 1% of the population directly, but also a much higher proportion (family and caregivers) indirectly. Although ASD is characterized by high prevalence of anxiety and poor gastrointestinal health, current treatment strategies are mainly focused on neurological symptomatic treatment, with little to no attention to gut health. Furthermore, many psychiatric drugs used for management of secondary neurological symptoms, are known to exacerbate gut health issues and neurological dysregulation across the gut-brain axis. Trace amines are neurotransmitter-like substances synthesized endogenously in the human brain – in trace amounts – but also in high abundance by the microbiome. Emerging evidence suggests dysregulation of the trace amine system in ASD. Since trace aminergic signalling is central to regulatory system homeostasis, we hypothesize targeting this system in the ASD context. Given the various sources of trace amines, we suggest that normalization of functional dysbiosis in terms of trace aminergic signalling – rather than microbial compositional dysbiosis – should be a focus in medicines development. In addition, a holistic consideration including also other factors at play in determining trace aminergic signalling outcome – such as receptor binding, enzymatic role players, etc. – is required to fully elucidate and therapeutically modify the pathophysiology of regulatory systems implicated in ASD. This review firstly provides a brief overview of trace amine dysregulation in ASD for context. Secondly, we formulate our hypothesis on how this may therapeutically address symptomology, with consideration of cellular and molecular mechanism interplay across the gut-brain axis. Finally, we provide a critical assessment of advances in therapeutics development and drug re-purposing, gaps in knowledge and priorities for medicines development going forward.